Room-temperature ferromagnetism of sol-gel-synthesized Sn1−x 57FexO2−(Delta) powders (2007)
ABSTRACT: We report unusual observations in the magnetic behavior of Sn1−x 57FexO2−(Delta) powders prepared by a sol-gel method. Mössbauer spectra showed three different sites for those irons in the SnO2 lattice. The samples seem to exhibit many sources of ferromagnetism, and the dominance of one of them greatly depends upon the synthesis conditions. In one sample, prepared using citric acid solution of metal Fe and annealed at 500 °C for two hours, we observed magnetization, but its room temperature Mössbauer spectrum did not show any magnetic component, suggesting that the ferromagnetism could not have originated from the iron ions but from magnetic defects. In another sample prepared from chloride acid solution of Fe2O3 and annealed at 600°C for six hours, a large magnetization and a sextet with broad lines were observed and the ferromagnetism was ascribed to iron impurities. In another sample prepared from citric acid solution of metal Fe but annealed at 650 °C for two hours, we observed an intensive magnetic sextet with sharp lines but small magnetization, suggesting the presence of hematite doped with tin.